Real transparency in medicine: Time to act. Issue 22 (29th July 2019) - Hudis, Clifford A.; Carlson, Robert W.
Abstract : Current methods of recording and reporting financial conflicts of interest are flawed and often result in inaccurate and inconsistent reporting by well‐intentioned individuals. To that end, this editorial identifies a number of specific current challenges for conflict‐of‐interest reporting along with potential solutions.